Renewal of the National Cervical Screening Program: health professionals' knowledge about screening of specific populations in NSW, Australia - Sally O Sweeney; Yan Cheng; Jessica R Botfield; Deborah J Bateson (Sax Institute, 2022)
Objectives: The National Cervical Screening Program was renewed in Australia from 1 December 2017, with the introduction of 5-yearly human papilloma virus (HPV) screening from age 25, and the release of updated national screening guidelines. This study aimed to determine health professional knowledge of the renewed screening program following implementation. Methods: We invited health professionals providing cervical screening in New South Wales (NSW), Australia, to complete an online survey in late 2018, to better understand their knowledge of the renewed screening guidelines, in particular regarding screening of specific populations, and to ascertain whether they had undertaken any educational activities relevant to the renewal. Results: A total of 241 responses were included in the data analysis. Health professionals demonstrated good knowledge of some aspects of the renewed program, including 64-85% correctly identifying limited indications for testing people younger than 25 years, 87% correctly identifying the need for completion of the Test of Cure protocol following treatment of high-grade lesions, and 71-80% correctly identifying management of symptomatic women. However several key knowledge gaps were identified including management of immune-deficient women (only 37% of respondents were aware of the need for 3-yearly screening), screening after total hysterectomy (56% were aware of guidance) and approximately 66% of health professionals correctly identifying indications for self-collected screening. One in ten health professionals had not undertaken any education specific to the renewal of the program. We found significant associations between knowledge levels and practitioner characteristics, including practitioners' frequency of access to the guidelines, specific educational activities undertaken and geographic location. Conclusion: Health professionals demonstrated strong knowledge of key aspects of the renewed National Cervical Screening program. However, our findings highlight some important gaps that may impact successful delivery of the program in Australia, and some significant associations between practitioner characteristics and knowledge levels, which will be important for education providers to note. Targeted educational interventions informed by these findings could support health professionals to better translate guidelines into practice and ensure successful delivery of this important public health program, particularly in regard to management of immune-deficient women, screening after hysterectomy and indications for self-collected screening.